Determinasi Politik dalam Proses Pemakzulan Presiden/Wakil Presiden - Fatahilla Alim (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The discourse regarding political determination in the process of impeaching the president and/or vice president is very interesting and deserves to be taken seriously. The author's hypothesis states that the process of impeaching the president and/or vice president is a political forum where at any time the MK has decided that the DPR's allegation that the President has committed a violation of the constitution is true, but to fully execute it will return to the MPR. This article tests this hypothesis using the normative juridical method, which involves analyzing legal norms, principles and doctrines through a positive legal approach. This study concludes that although the main characteristic of impeaching the president and/or vice president in a presidential system is a difficult clause, the choice to prioritize the legitimacy of the political forum must also be followed by a rational process and composition.